PORTEC-4a: international randomized trial of molecular profile-based adjuvant treatment for women with high-intermediate risk endometrial cancer. Issue 12 (12th October 2020) - van den Heerik, Anne Sophie V M; Horeweg, Nanda; Nout, Remi A; Lutgens, Ludy C H W; van der Steen-Banasik, Elzbieta M; Westerveld, G Henrike; van den Berg, Hetty A; Slot, Annerie; Koppe, Friederike L A; Kommoss, Stefan; Mens, Jan Willem M; Nowee, Marlies E; et al.
Abstract : Background: Vaginal brachytherapy is currently recommended as adjuvant treatment in patients with high-intermediate risk endometrial cancer to maximize local control and has only mild side effects and no or limited impact on quality of life. However, there is still considerable overtreatment and also some undertreatment, which may be reduced by tailoring adjuvant treatment to the patients' risk of recurrence based on molecular tumor characteristics. Primary objectives: To compare the rates of vaginal recurrence in women with high-intermediate risk endometrial cancer, treated after surgery with molecular-integrated risk profile-based recommendations for either observation, vaginal brachytherapy or external pelvic beam radiotherapy or with standard adjuvant vaginal brachytherapy Study hypothesis: Adjuvant treatment based on a molecular-integrated risk profile provides similar local control and recurrence-free survival as current standard adjuvant brachytherapy in patients with high-intermediate risk endometrial cancer, while sparing many patients the morbidity of adjuvant treatment and reducing healthcare costs. Trial design: A multicenter, international phase III randomized trial (2:1) of molecular-integrated risk profile-based adjuvant treatment (experimental arm) or adjuvant vaginal brachytherapy (standard arm). Major inclusion/exclusion criteria: Women aged 18 years and over with a histological diagnosis of high-intermediate risk endometrioid endometrial cancer after total abdominal or laparoscopic hysterectomy and bilateral salpingo-oophorectomy. High-intermediate risk factors are defined as: (i) International Federation of Gynecology and Obstetrics stage IA (with invasion) and grade 3; (ii) stage IB grade 1 or 2 with age ≥60 and/or lymph-vascular space invasion; (iii) stage IB, grade 3 without lymph-vascular space invasion; or (iv) stage II (microscopic and grade 1). Endpoints: The primary endpoint is vaginal recurrence. Secondary endpoints are recurrence-free and overall survival; pelvic and distant recurrence; 5-year vaginal control (including treatment for relapse); adverse events and patient-reported symptoms and quality of life; and endometrial cancer-related healthcare costs. Sample size: 500 eligible and evaluable patients. Estimated dates for completing accrual and presenting results: Estimated date for completing accrual will be late 2021. Estimated date for presentation of (first) results is expected in 2023. Trial registration: The trial is registered at clinicaltrials.gov (NCT03469674 ) and ISRCTN (11659025).